Ultrasound and MRI features of lipomatosis of the median nerve: A case study - GÜNDOĞMUŞ, CEMAL AYDIN; BUĞDAYCI, ONUR (MARMARA UNIV, FAC MEDICINE, 2018)
We present a case of a 10 year-old girl with slowly enlarging, painless mass at the volar aspect of her left hand. The lesion had been present since infancy. Diagnosis was lipomatosis of the median nerve which is a very rare, benign tumor involving peripheral nerves. Magnetic resonance imaging (MRI) and ultrasound (US) features of this lesion are discussed.
Keywords: Median nerve lipomatosis; Fibrolipomatous hamartoma; Congenital tumor; Peripheral nerve; LIPOFIBROMATOUS HAMARTOMA; FIBROLIPOMATOUS HAMARTOMA